On the Truth Comissions and the application of justice processes of democratic trasition - Springer, Natalia (Desafíos, 2017)
A widely accepted definition of what a Truth Commission is, is presented as an introduction far this article. Thedefinítion isfollowed bya description of its five main functions: to clarify the truth; to deal with the need of victims; tocontribute to the process of justice administration; topropoSe institutional reforms and tomove forward in thedevelopmentof reconcilement mechanisms. Furthermore, the article analyses comparativel yexam ples of existing Truth Commissions, and acuses on the possib fe birth of a fourth generatíon ofTruth Commissions. The lattercould be characterised by their establishment in the middle of a non-resolved conflict, as a too/ far ’restorativedemocracy’ and far peace building. The ana/ ysis presented here highlights the need far minimal conditions far a Truth Commission to be successful. Those conditions being: an overafl consensus between parts, a cease-fire, and the support of civil society and the lnternationa/ Community. The author concludes with a brief sketching of the Sierra Leone case, emphasising on its methodological vafue.